2008
DOI: 10.1080/10253890701794445
|View full text |Cite
|
Sign up to set email alerts
|

Differential sensitisation to central cardiovascular effects of angiotensin II in rats with a myocardial infarct: Relevance to stress and interaction with vasopressin

Abstract: The purpose of the present study was to elucidate if rats with myocardial infarction manifest altered responsiveness to central cardiovascular effects of low doses of angiotensin II (ANG II), and if ANG II and vasopressin (VP) cooperate in the central regulation of cardiovascular functions at rest and during stress. Conscious Sprague-Dawley rats with myocardial infarction induced by left coronary artery ligation, or sham-ligated (SL) controls were infused intracerebroventricularly with artificial cerebrospinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 46 publications
2
19
0
Order By: Relevance
“…In previous studies, it was demonstrated that this effect significantly depends on the activation of the brain renin-angiotensin system as it could be abolished by ICV administration of AT1 receptor blockers and potentiated by central administration of Ang II [1719]. The present study shows that significant attenuation of exaggerated cardiovascular responses to acute stress may be achieved both in infarcted and in chronically stressed rats by oral administration of captopril.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…In previous studies, it was demonstrated that this effect significantly depends on the activation of the brain renin-angiotensin system as it could be abolished by ICV administration of AT1 receptor blockers and potentiated by central administration of Ang II [1719]. The present study shows that significant attenuation of exaggerated cardiovascular responses to acute stress may be achieved both in infarcted and in chronically stressed rats by oral administration of captopril.…”
Section: Discussionsupporting
confidence: 67%
“…We have also found that vasopressin and stimulation of V1 receptors participate in Ang II-induced potentiation of the cardiovascular responses to acute stress in infarcted rats [18, 19]. Thus, reduction of the cardiovascular responses to acute stress by captopril could result from its inhibitory effect on generation of Ang II in vasopressin secreting neurons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, oxytocin produced opposite effects to vasopressin (Dobruch et al 2005;Cudnoch-Jędrzejewska et al 2008;Stojicić et al 2008). For instance, blockade of oxytocin receptors enhanced the pressor and tachycardic responses to stress in the sham-operated rats while being ineffective in the infarcted rats, whereas blockade of V1 receptors with d(CH 2 ) 5 Tyr(Me) 2 ,Ala-NH 2 9 ]AVP was not effective in the sham-operated rats but it markedly strengthened the pressor and tachycardic responses to stress during the post-infarct state (Dobruch et al 2005;Cudnoch-Jędrzejewska et al 2007).…”
Section: Brain Oxytocin Stress and Circulation 523mentioning
confidence: 93%
“…The rate of ICV infusion of oxytocin used in the present study (100 ng/h) may be considered to be relatively low in comparison to the doses administered by other authors. Oxytocin was infused at this rate in order to match the rate of vasopressin infusion that has been used in our previous investigations (Dobruch et al 2005;Cudnoch-Jędrzejewska et al 2008). Therefore, it cannot be excluded that a higher dose of oxytocin would affect function of the cardiovascular system under baseline conditions.…”
Section: Effects Of Exogenous Oxytocinmentioning
confidence: 98%